A REVIEW ON CONSUMERS' PURCHASING PATTERNS FOR ORGANIC FOOD PRODUCTS (International Journal of Food and Nutritional Sciences, 2022)
As environmental concerns increase, consumers are paying more attention to eco-friendly qualities in goods. People are becoming more health conscious and are placing a higher value on health-related factors when making product choices. The shift in consumer food consumption patterns also seems to pose a significant threat to leading a healthy life. Using more and more chemicals and fertilisers is bad for everyone. Hence, organic farming gained momentum in many regions. Health awareness, environmental concerns, subjective norms, and a willingness to pay are postulated as primary motivators for the purchase or consumption of organic products. The future of the organic product market hinges on customer demand, thus research into the sector must be conducted with the end user in mind. The purpose of this research report is to learn how people in the Delhi-National Capital Region shop for organic food items. The purpose of this research is to determine what factors most strongly affect consumers' perceptions of organic food products and their decisions to buy them.